2013
DOI: 10.3390/en6115807
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Measurements from Basic Meteorological Stations for Wind Speed Forecasting

Abstract: This research presents a comparative analysis of wind speed forecasting methods applied to perform 1 h-ahead forecasting. The main significant development has been the introduction of low-quality measurements as exogenous information to improve these predictions. Eight prediction models have been assessed; three of these models [persistence, autoregressive integrated moving average (ARIMA) and multiple linear regression] are used as references, and the remaining five, based on neural networks, are evaluated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The number of neurons in each layer is reported in Table 3. After an optimization process oriented to minimize the Mean Square Error, it was verified that for the hidden layer (layer 2) the best value corresponds to the mean of the neurons between the input and output layer [43]. In the first layer the hyperbolic tangent sigmoid transfer function (TANSIG) [44] was applied and in the second layer the linear transfer function (PURELIN) [45] was used.…”
Section: The Artificial Neural Network Methodsmentioning
confidence: 99%
“…The number of neurons in each layer is reported in Table 3. After an optimization process oriented to minimize the Mean Square Error, it was verified that for the hidden layer (layer 2) the best value corresponds to the mean of the neurons between the input and output layer [43]. In the first layer the hyperbolic tangent sigmoid transfer function (TANSIG) [44] was applied and in the second layer the linear transfer function (PURELIN) [45] was used.…”
Section: The Artificial Neural Network Methodsmentioning
confidence: 99%
“…The empirically retrieved 10-hour time-window interval was found to be a convenient trade-off to the model, which comprises sufficient information diversity and low cross-correlation between Train and Test datasets. Our choice is also supported by existing studies on the auto-correlation decay in wind speed time series [24].…”
Section: Train-test-validation Strategymentioning
confidence: 91%
“…The equation (8) presented in the GA is also adopted as the fitness function in the MEA. The other detailed parameters of the MEA searching are listed as follows:…”
Section: Mlp Neural Network Optimized By Meamentioning
confidence: 99%
“…Their experimental results showed that the RT based forecasting methods were able to obtain very satisfactory results. Palomares-Salas et al [8] compared eight models for the wind speed one-hour ahead forecasting. In the study, the PM (Persistent Model), the ARIMA model, the MLR (Multiple Linear Regression) and five different types of neural networks were estimated.…”
Section: Introductionmentioning
confidence: 99%